Effects of Soursop (Annona muricata ) Lea f Water Extract (SLWE) on Body Weight, Leptin and TNF α Plasma Levels of Rats with High Fat and High Fructose (HFHF) Diet. - Dini Sri Damayanti (Journal of Global Pharma Technology, 2019)
Abstract Background: Soursop leaves believed to be able to lose weight. The aim of the study was to prove that SLWE had an effect on body weight, leptin and TNF α plasma level in mice with the HFHF diet . Methods:The study used post test group design only. Male Wistar rats aged 8-10 weeks weighing 175-200g, healthy, 25 were divided into 5 groups by simple random sampling. Normal groups (N) , Positive groups (P) were given a HFHF 10% diet, treatment group (T1), T2, and T3 ( HFHF diet + SLWE at dose of 100 mg / kg bw, 200 mg / kg bw, and 400 mg / kg bw). The diet and extract were given for 10 weeks. Measurement of body weight and weighing the amount of food consumed were carried out every week. Measurement of plasma leptin and TNF α levels using the ELISA method. Statistical analysis using ANOVA and Kruskal Wallis test with a confidence level p <0.05. Results : SLWE at all doses increased the amount of intake compared to P and N groups (p <0.05).Giving SLWE at dose of 400 mg/kgbw causes a slowdown in weight gain (p> 0.05), increase levels of plasma leptin than P group. There was a tendency to decrease TNF α plasma levels with an increase in the dose of the extract (p>0.05). Conclution : Giving SLWE in HFHF diet-induced mice increased appetite, increased Leptin levels, and tendency to decreased weight gain and TNF α levels.Keyword : Soursop leaf, Weight gain, Leptin, TNF α, High Fat-High Fructose Diet